Electrochemical Detection of Hydroxychloroquine Sulphate Drug using CuO/GO Nanocomposite Modified Carbon Paste Electrode and its Photocatalytic Degradation - G. S. Shaila; Dinesh Patil; Naeemakhtar Momin; J. Manjanna (전기화학회지, 27(1), 2024)
The antimalarial drug hydroxychloroquine sulphate (HCQ) has taken much attention during the first COVID-19 pandemic phase for the treatment of severe acute respiratory infection (SARI) patients. Hence it is interest to study the electrochemical properties and photocatalytic degradation of the HCQ drug. Copper oxide (CuO) nanoparticles, graphene oxide (GO) and CuO/ GO NC (nanocomposite) modified carbon paste electrodes (MCPE) are used for the detection of HCQ in an aqueous medium. Electrochemical behaviour of HCQ (20 μM) was observed using CuO/MCPE, GO/MCPE and CuO/GO NC/MCPE in 0.1 M phosphate buffer at pH 7 with a scan rate of 20 to 120 mV s−1 by cyclic voltammetry (CV). Differential pulse voltammetry (DPV) of HCQ was performed for 0.6 to 16 μM HCQ. The CuO/GO NC/MCPE showed a reasonably good sensitivity of 0.33 to 0.44 μA μM cm–2 with LOD of 69 to 92 nM for HCQ. Furthermore, the CuO/GO NC was used as a catalyst for the photodegradation of HCQ by monitoring its UV-Vis absorption spectra. About 98% was degraded in about 34 min under visible light and after 4 cycles it was 87%. The improved photocatalytic activity may be attributed to decrease in bandgap energy and enhanced ability for the electrons to migrate. Thus, CuO/GO NC showed good results for both sensing and degradation applications as well as reproducibility. KCI Citation Count: 0